Insight into the role of histidine in RNR motif of protein component of RNase P of M. tuberculosis in catalysis. Issue 3 (24th January 2016) - Singh, Alla; Ramteke, Anup K.; Afroz, Tariq; Batra, Janendra K.
Abstract: RNase P, a ribonucleoprotein endoribonuclease, is involved in the 5′ end processing of pre‐tRNAs, with its RNA component being the catalytic subunit. It is an essential enzyme. All bacterial RNase Ps have one RNA and one protein component. A conserved RNR motif in bacterial RNase P protein components is involved in their interaction with the RNA component. In this work, we have reconstituted the RNase P of M. tuberculosis in vitro and investigated the role of a histidine in the RNR motif in its catalysis. We expressed the protein and RNA components of mycobacterial RNase P in E. coli, purified them, and reconstituted the holoenzyme in vitro . The histidine in RNR motif was mutated to alanine and asparagine by site‐directed mutagenesis. The RNA component alone showed activity on pre‐tRNA ala substrate at high magnesium concentrations. The RNA and protein components associated together to manifest catalytic activity at low magnesium concentrations. The histidine 67 in the RNR motif of M. tuberculosis RNase P protein component was found to be important for the catalytic activity and stability of the enzyme. Generally, the RNase P of M. tuberculosis functions like other bacterial enzymes. The histidine in the RNR motif of M. tuberculosis appears to be able to substitute optimally for asparagine found in the majority of the protein components of other bacterial RNase P enzymes. © 2016 IUBMB Life, 68(3):178–189, 2016